Algae: a frontline photosynthetic organism in the microplastic catastrophe. (November 2022) - Manzi, Habasi Patrick; Abou-Shanab, Reda A.I.; Jeon, Byong-Hun; Wang, Junling; Salama, El-Sayed
Abstract : Recalcitrancy in microplastics (MPs) contributes to white pollution. Bioremediation can remove MPs and facilitate environmental sustainability. Although recent studies have been conducted on the interaction of algae and MPs, the role of algae in MP removal with the simultaneous implementation of 'omics studies has not yet been discussed. Here, we review the adverse effects of MPs on the environment and possible approaches to remove them from the aquatic environment by using algae. We highlight the mechanism of MP biodegradation, the algal species that have been used, and how these are affected by MPs. We propose that algomics, characterization of biodegrading enzymes, and genetic engineering could be effective strategies for optimizing MP degradation. Highlights: Microplastics (MPs) pollution is a challenge to both environmental and human health. Recent studies on the interaction of algae and MPs have contributed to the understanding of algal responses to the effects of MPs. Aggregation of algae and MPs is a key for MP removal approaches. Application of algae with 'omics and genetic engineering could be an effective strategy for enhancing MP biodegradation.